Design and develop a generic cut-through switch / Noraini Nazaruddin - Noraini , Nazaruddin (2001)
Today's advancement in network is related to the advancement of packet switching technology. Switching directs network traffic in an efficient manner – it sends information directly from the port of origin to only its destination port. Without switching, many networks are experiencing bandwidth shortages because of an increase in traffic due to the increased numbers of users, the amount of data transported between client/server applications, and the inefficient traffic patterns of some networks. Transmission of data from one destination to another is unguaranty successful. Sometimes the data will lost or conupted during transmission to destination port. To make data more reliable, we need to improved switch operation. Latency, throughput and delay can effect network performances. To resolve this problem, remodeling the switch will help we find out the weakness of the switch, so from that we can enhance the functional of switch. Cut through switching method is used in this project to improve network performances. To make packet more reliable and prevent packet loss during transmission in network, the buffer will be manage properly and effectively. This project also emphasized on switch fabric, buffer, input and output port to make transmission of data more efficient To prevent waste of buffer, divide packet into smaller partition (eg. 64 bytes) is required. The scope of this project is to design and develop a generic cut-through switch using Java tools. The switch is modeled from Ethernet cut through switch which is operates at LAN. Transmission packet is based on Ethernet header MAC address. Ethernet switch architectures are modeled from crossbar approaches. Dummy packet is use for packer generator. The expected outcome for this project is a simulator that show how cut-through switch work and a graph that show the ratio of frames dropped.